'The best and the brightest': widening participation and social justice in contemporary English social work education. Issue 3 (4th May 2021) - Hanley, Joe
ABSTRACT: Social work education in England has a long track record of success in widening participation to disadvantaged student populations. However, more recently these successes have instead been cast as a burden that is negatively impacting on the calibre of students entering the profession. Alongside this reconceptualisation, new fast-track models of education have been introduced, providing a quicker and more financially supported a route of entry to the profession. This article critically examines the changing nature of widening participation in social work education and how fast-track social work programmes are perpetuating the inequalities that are inherent at all levels of the English educational system. This discussion is shown to have implications for widening participation policy agenda beyond social work. The concerns that are raised should be of interest to any other jurisdictions considering the possibility of a fast-track approach to social work education. A social justice approach-based bringing students together is proposed as an alternative and preferable model of social work education.